2012
DOI: 10.1017/s1751731111002710
|View full text |Cite
|
Sign up to set email alerts
|

The effect of N-fertilisation rate or inclusion of red clover to timothy leys on fatty acid composition in milk of dairy cows fed a commercial silage : concentrate ratio

Abstract: The aim of this experiment was to, under typical Swedish production conditions, evaluate the effects of grass silages subjected to different N-fertilisation regimes fed to dairy cows on the fatty acid (FA) composition of their milk, and to compare the grass silages in this respect to red clover-dominated silage. Grass silages made from first year Phleum pratense L. leys subjected to three N-fertilisation regimes (30, 90 and 120 kg N/ha, designated G-30, G-90 and G-120, respectively) and a mixed red clover-gras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
(44 reference statements)
4
3
0
Order By: Relevance
“…The recoveries on the two red clover diets in Exp. 1 was similar to results reported by Dewhurst et al (2003b) and Arvidsson et al (2012) for cows on red clover-grass silage. However, the recovery of C18:3n-3 on S3 in Exp.…”
Section: Effect Of Botanical Compositionsupporting
confidence: 90%
See 1 more Smart Citation
“…The recoveries on the two red clover diets in Exp. 1 was similar to results reported by Dewhurst et al (2003b) and Arvidsson et al (2012) for cows on red clover-grass silage. However, the recovery of C18:3n-3 on S3 in Exp.…”
Section: Effect Of Botanical Compositionsupporting
confidence: 90%
“…This result is found in several previous studies (e.g. Arvidsson et al, 2012;Dewhurst et al, 2003b;Jayanegara et al, 2011), and one suggested explanation are a higher ruminal disappearance the more double bounds that are present in the FA.…”
Section: Effect Of Botanical Compositionsupporting
confidence: 88%
“…Similarly, Elgersma et al (2005) found higher concentrations of individual FAs and TFA for treatments involving higher levels of added N. However, the latter authors did not find any fertilization-related differences in the relative proportions of the different FAs, which is consistent with the results obtained in this work (Table II). In a study with similar N-fertilization levels as in this work, Arvidsson et al (2012) observed the highest TFA concentration in grass fertilized with 90 kg N ha (1 , the lowest in grass fertilized with 30 kg N ha (1 , and an intermediate TFA concentration in grass fertilized with 120 kg N ha (1 .…”
Section: Effect Of N-fertilizationsupporting
confidence: 77%
“…Vanhatalo et al (2007) showed a greater increase in 18:3 content of milk fat for early-cut red clover silage in comparison with late-cut red clover silage. Dewhurst et al (2003b) observed intermediate levels of 18:3 in milk when feeding mixtures of grass silage and red clover silage; Arvidsson et al (2012) found only small but statistically significant increases when feeding a mixture of timothy and red clover silage.…”
Section: Milk Fatty Acidsmentioning
confidence: 93%